Pochonia cordycepisociata, a new species associated with Chinese cordyceps in Tibet, China - Huang, Hai; Wang, Mu; Zhang, Luo; Yue, Hai Mei; Gong, Wen Feng; Cai, Lei (Phytotaxa, 2015)
During a survey of fungi associated with the Chinese cordyceps (Ophiocordyceps sinensis) collected from Tibet, China, a new species, Pochonia cordycepisociata was isolated from the sclerotium of O. sinensis. It is characterized and different from other Pochonia species by its aggregated compact hyphae, slender phialides, global to ellipsoid conidia and the absence of dictyochlamydospores. A multi-locus (ITS, SSU, LSU, TEF, RPB1 and RPB2) phylogenetic analysis supported its independence from other species. A synopsis of the morphological characters of the new species and its related taxa is provided.